2012
DOI: 10.4321/s1130-01082012000300004
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analysis of clinician accuracy in the diagnosis of benign anorectal pathology: the value of clinical information

Abstract: Aim: the prevalence of anorectal disorders in general population is high. The aim of this study was to analyze the influence of clinical symptoms on diagnostic accuracy for benign anorectal pathology among different specialists and evaluate the relation ship between diagnostic accuracy and years of professional expe rience.Methods: seven typical cases were selected. In a first interview, participants were shown images and asked to make a diagnosis. Afterwards, images with additional information (clinical sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Other research suggests that the accuracy of AF diagnosis depends greatly on the skills of the examining physician. One study from Spain demonstrated that surgeons can identify AF with very high reliability, but primary care providers were much less likely to correctly identify an AF lesion [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Other research suggests that the accuracy of AF diagnosis depends greatly on the skills of the examining physician. One study from Spain demonstrated that surgeons can identify AF with very high reliability, but primary care providers were much less likely to correctly identify an AF lesion [27]. …”
Section: Discussionmentioning
confidence: 99%
“…In a recent study performed in Spain, the diagnostic accuracy of general practitioners in patients referred to specialists was assessed. Interestingly, the diagnosis of haemorrhoids was much better than that of anal fistula or fissure, the Kappa index in the latter diagnosis being particularly poor [10], and participants in our recent study also found anal fissure to be especially difficult to recognize [7]. This question is especially relevant when coloproctologists have to distinguish between anal fissure and haemorrhoids.…”
mentioning
confidence: 99%
“…In a recent study our group provided evidence that the analysis of symptoms has a greater influence on diagnostic accuracy than years of clinical experience [7]. Indeed, when appropriate questions are asked in a structured format, the physical examination is only a secondary element in making the diagnosis.…”
mentioning
confidence: 99%